Elemgasem nubilus: a new brachyrostran abelisaurid (Theropoda, Ceratosauria) from the Portezuelo Formation (Upper Cretaceous) of Patagonia, Argentina. (5th September 2022) - Baiano, Mattia A.; Pol, Diego; Bellardini, Flavio; Windholz, Guillermo J.; Cerda, Ignacio A.; Garrido, Alberto C.; Coria, Rodolfo A.
Abstract: Abelisaurids are medium–large‐sized theropod dinosaurs that were predominant in the carnivorous fauna during the Late Cretaceous of Gondwana. These predators are abundant in the Cretaceous fossil strata of Patagonia, which yield the best record for this group. In the Late Cretaceous, abelisaurids appear in almost all regions of Gondwana and in all stages, except for the Coniacian, in which they are globally unknown. Here we describe a new abelisaurid, Elemgasem nubilus gen. et sp. nov., from the Portezuelo Formation (Turonian–Coniacian), Patagonia, Argentina. The palaeohistology of the appendicular bones of Elemgasem shows that the holotype was a subadult individual, but had achieved sexual maturity. This taxon is based on several axial and appendicular elements, and is diagnosed by the presence of a marked pattern of rugosity on the lateral surface of the fibula and a dorsoventrally deep lateral wall of the calcaneum. Moreover, the posterior caudal vertebrae have a morphology slightly different from any other abelisaurid. Elemgasem nubilus is recovered as an unstable taxon within Brachyrostra, given that it was recovered as sister taxon of Furileusauria or in several positions within this clade. Despite the problematic phylogenetic relationships of Elemgasem nubilus, it is important because it is the first abelisaurid from the Turonian–Coniacian interval and it increases the diversity of this theropod family at a time of marked turnover in the tetrapod fauna of South America, global climate change, and mass extinction events recorded worldwide in the marine realm.